Clinicoepidemiological Study of Different Types of Warts. (7th March 2016) - Ghadgepatil, Shruti S.; Gupta, Sanjeev; Sharma, Yugal K.
Abstract : Background . Warts are cutaneous and, sometimes, mucosal lesions caused by one of the several human papilloma viruses. Aim . Assessment of the clinicoepidemiological aspects of warts. Materials and Methods . One hundred consecutive patients of warts presenting to the department of our institution were assigned two broad locational groups: genital and nongenital warts, the latter subdivided into common, plane, palmoplantar, mosaic, and digitate/filiform. Results . Ninety had nongenital and 10 had genital warts in our study; common (42%), palmoplantar (20%), and plane (18%) were the common types of the nongenital warts. All the genital warts were acuminate. In the second decade, the commonest age group, encompassed all patients of mosaic, 40% of palmoplantar, and 20% of genital warts. Overall male (66%) preponderance xisted. All cases of filiform warts were males. Mosaic warts affected females more commonly. Students (32%), laborers (28%), and housewives (16%) were the usual occupations. Cosmetic concern (92%), pain (16%), and itching (15%) were the common complaints. All patients of genital warts sought treatment within 6 months. Conclusions . Common, palmoplantar, and plane warts were the common types of nongenital warts. Overall prevalence peaked during the second decade but one-third of the cases of plane warts occurred during the first. Extremities were the most common sites (66.7%); face was the next commonly (23%) involved.